2017
DOI: 10.14283/jpad.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Practice Effects and Amyloid Deposition: Providing Information Above and Beyond Baseline Cognition

Abstract: Background: Practice effects, which are improvements in cognitive test scores due to repeated exposure to testing materials, may provide information about Alzheimer’s disease pathology, which could be useful for clinical trials enrichment. Objectives: The current study sought to add to the limited literature on short-term practice effects on cognitive tests and their relationship to amyloid deposition on neuroimaging. Participants: Twenty-seven, non-demented older adults (9 cognitively intact, 18 with mild cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Reduced practice effects on episodic memory tests have been observed previously in preclinical AD groups from AIBL and other prospective studies, [8][9][10] although the magnitude of these reductions (d = 0.4) have been only slightly larger than those observed between the current sample of Aβ-ε4 carriers and non-carriers. Recent investigations into Aβ-individuals have identified subsets with faster Aβ accumulation, 7 particularly in ε4 carriers, 6 although no study has observed memory decline in either AD risk groups when individuals who progressed to MCI/AD were excluded.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Reduced practice effects on episodic memory tests have been observed previously in preclinical AD groups from AIBL and other prospective studies, [8][9][10] although the magnitude of these reductions (d = 0.4) have been only slightly larger than those observed between the current sample of Aβ-ε4 carriers and non-carriers. Recent investigations into Aβ-individuals have identified subsets with faster Aβ accumulation, 7 particularly in ε4 carriers, 6 although no study has observed memory decline in either AD risk groups when individuals who progressed to MCI/AD were excluded.…”
Section: Discussionsupporting
confidence: 44%
“…In the Australian Imaging, Biomarkers and Lifestyle (AIBL) study, CNs completed seven neuropsychological assessments over 108 months providing greater power than previous investigations of Aβ– groups to understand the effects of ε4 on cognition 3,7 . However, prospective investigations of cognitive change in AIBL, and in similar longitudinal cohorts, now show that in Aβ+ CNs, episodic memory remains stable over 5 to 6 years, whereas in matched Aβ– CNs, memory improves substantially over the same interval (ie, a practice effect) 8–11 . Reduced practice effects are proposed to be a strong clinical marker of early Alzheimer's disease (AD) pathologic changes in preclinical AD, 9,11 and are therefore likely to occur in CN Aβ– ε4 carriers.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of learning curves over short time intervals using smartphones may serve as a cost‐effective screening tool to enrich samples for AD biomarker positivity prior to expensive assays. For example, a clinical study found that lower practice effects over 1 week were associated with a nearly 14 times higher odds of being Aβ+ on a composite measure using [ 18 F]flutemetamol 81 . Future work with larger CN samples and further optimized learning paradigms may show similar discriminability properties of learning curves to AD biomarker positivity in a preclinical sample.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a clinical study found that lower practice effects over 1 week were associated with a nearly 14 times higher odds of being Aβ+ on a composite measure using [ 18 F]flutemetamol. 81 Future work with larger CN samples and further optimized learning paradigms may show similar discriminability properties of learning curves to AD biomarker positivity in a preclinical sample. Capturing learning curves over short intervals using remote smartphone-based assessment may provide a more rapid means of assessing whether a novel treatment has beneficial effects on cognition.…”
Section: Work Using a Web-based Version Of Fnamementioning
confidence: 96%
“…It has been shown that subjects with late-life cognitive disorders show reduced practice effects as compared to their healthy peers [81]. Furthermore, diminished practice effects may predict future decline, a future diagnosis of MCI, and greater brain-related pathology [82][83][84].…”
Section: Novel Neuropsychological Methods To Characterize Early Cogni...mentioning
confidence: 99%